Climatic Influences on Summer Use of Winter Precipitation by Trees. Issue 10 (12th May 2022) - Goldsmith, Gregory R.; Allen, Scott T.; Braun, Sabine; Siegwolf, Rolf T. W.; Kirchner, James W.
Abstract: Trees in seasonal climates may use water originating from both winter and summer precipitation. However, the seasonal origins of water used by trees have not been systematically studied. We used stable isotopes of water to compare the seasonal origins of water found in three common tree species across 24 Swiss forest sites sampled in two different years. Water from winter precipitation was observed in trees at most sites, even at the peak of summer, although the relative representation of seasonal sources differed by species. However, the representation of winter precipitation in trees decreased with site mean annual precipitation in both years; additionally, it was generally lower in the cooler and wetter year. Together, these relationships show that precipitation amount influenced the seasonal origin of water taken up by trees across both time and space. These results suggest higher turnover of the plant‐available soil‐water pool in wetter sites and wetter years. Plain Language Summary: In the middle of a hot and dry summer, we often think that a large rain event can "rescue" a forest from drought. However, it is not clear whether trees can or do consistently use the water from summer rains. A growing body of research indicates that over the course of the summer growing season, trees take up significant amounts of water that originated as winter snow or rain. We studied the seasonal origins of the water taken up by three common tree species (beech, oak and spruce) in forest sites across Switzerland in two different years. Our results demonstrate that trees at most sites use some water from winter snow and rain, even at the height of summer, although there were differences among species and sites. The water sources used by trees likely reflect a combination of the amount and timing of winter and summer precipitation, the rate at which that precipitation moves through the soil, and the distribution of the tree roots that take up the water. Determining the seasonal origin of water used by trees, as well as why it may vary over time and space, can help us better anticipate the effects of global climate change. Key Points: We determined the representation of water originating from winter versus summer precipitation in the xylem of common Swiss trees Water originating from winter precipitation was observed in trees at most sites, even at the height of summer, but varied among species Climate and species appear to be key controls over spatial and inter‐annual variations in the seasonal origins of water used by trees